FAKTOR DOMINAN PENYEBAB TERJADINYA BBLR DI RSUD DR. WAHIDIN SUDIRO HUSODO DAN RSI SAKINAH MOJOKERTO - Mumairoh, Laifah; Ma’rifah, S.ST., M.Kes, Asirotul (JURNAL KEPERAWATAN BINA SEHAT, 2016)
The incidence of LBW in Indonesia is still quite high. LBW can be caused by various factors, such as maternal age pregnancy and anemia in pregnancy. LBW will cause a variety of health effects, especially during child development. Some children are born LBW hampers the growth of the brain, have a high risk of infectious diseases, as well as physical barriers growth. The purpose of this study is to factor the dominant cause of LBW in hospitals Dr. Wahidin Sudirohusodo Mojokerto. This research was a descriptive. The population is all newborns who experience LBW in hospitals Wahidin Sudiro Husodo and RSI Sakinah Mojokerto June-July 2016 as many as 12 infants, samples were taken by using consecutive sampling technique and obtained a sample of 12 respondents. The research variables are dominant factors cause of LBW. Collecting data using documentation technique, after the data is collected to analyze the data by editing, coding and tabulating. The results showed that the majority of mothers with LBW infants aged 20-35 years by 9 respondents (75%), the majority of babies born at gestational age preterm (<37 weeks) were 9 respondents (75%) and the majority of mothers who gave birth to LBW babies do not have anemia in pregnancy as many as 7 people (58.3%). Based on the results of the study showed that age pregnancy is the most dominant factor affecting the incidence of low birth weight in newborns. This is because the growth of the fetus in the womb depends on the nutrient intake during in uterus. Should health workers can provide counseling or counseling to pregnant women during antenatal care, especially in women with high risk.Keywords: Low Birth Weight